Optimum depth for the introduction of crush pillars at Impala Platinum Mine - Maphosa, Tatenda John (My University, 2022)
Impala Mine planned to introduce 4 m x 2 m crush pillars on the UG2 Reef, and were interested in finding the depth where such pillars can be safely used. These pillars have the benefit of increasing the extraction ratio whilst reducing the risk of pillar bursting. The mine provided rock samples composed of four rock types namely: anorthosite, chromitite, pegmatoid and pyroxenite for geomechanical testing. In addition, a database of previous tested rock specimens was provided. The rock samples provided for testing were used to determine post-peak behaviour under triaxial loading conditions, as well as Uniaxial Compressive and Brazilian Tensile strengths. During testing it was apparent that the testing machine was showing incorrect deformation readings. Investigations showed the problem to be the axial transducer, and it was replaced. Subsequently, the results of the correct laboratory tests were used as input parameters for a FLAC3D numerical model. Two scenarios for the crush pillar were modelled. Scenario 1 assumes the presence of a 2 m siding and scenario 2 assumes the pillar is right next to the gully. The model assumed repeating geometries of pillars and the results suggested peak strengths of 104 MPa and 79 MPa for scenario 1 and 2, respectively, and a residual strength of about 12 MPa for both scenarios. The investigations showed that the 4 m x 2 m crush pillars can be safely introduced at depths of 663 m and 476 m for pillars with and without a siding, respectively. The pillars can be introduced at shallower depths (from 357 m for pillar with a siding and 272 m for the one without a siding) with caution as the available stress may not be sufficient.
A research dissertation submitted in fulfilment of the requirements for the degree of Master of Science in Engineering to the Faculty of Engineering and the Built Environment, School of Mining Engineering, University of the Witwatersrand, Johannesburg, 2022